DAMPAK INOVASI INTERNET BANKING (E-BANKING) TERHADAP KINERJA BANK UMUM SYARIAH DI INDONESIA - hamdi, luthfia ahluljannati (Diponegoro Journal of Islamic Economics and Business, 2025)
One of the non-cash transactions implemented in Islamic Commercial Banks in Indonesia is internet banking (e-banking) services. This study aims to determine the impact of Internet Banking (E-Banking) innovation on the financial performance of Islamic Commercial Banks in Indonesia. The population of this study consists of all Islamic Commercial Banks in Indonesia in 2013 to 2023. According to the Financial Services Authority's Islamic Banking Statistics Data in 2013, there were 11 Islamic commercial banks in Indonesia. As a result of the merger of several Islamic banks, this study obtained data from 6 Islamic commercial banks as samples. The results of the study indicate that the Implementation of Internet Banking (IB) has a negative effect on Return on Assets (ROA). This is thought to be due to costs associated with internet banking services, such as infrastructure, maintenance, and human resources, which require higher expenditures compared to the income generated from the internet banking service itself. In addition, the increasing frequency of internet banking service updates has the potential to reduce bank profitability (ROA) due to the high costs associated with device updates, which in turn reduce income. Overall, the costs paid by Islamic banks to provide internet banking services involve various components of quite large costs, ranging from system development and maintenance to transaction costs, security, and sharia compliance. SIZE, DEPOSIT, NPF and BOPO affect the performance of Islamic commercial banks in Indonesia. The empirical findings of this study have significance for the development of e-banking which will bring long-term benefits to the entire banking industry in Indonesia.